2007
DOI: 10.1111/j.1468-1293.2007.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of complementary and alternative medicines among a multistate, multisite cohort of people living with HIV/AIDS

Abstract: Objective The aim of the study was to assess the prevalence of and factors associated with use of complementary or alternative medicine (CAM) in a multistate, multisite cohort of HIV‐infected patients. Methods During 2003, 951 adult patients from 14 sites participated in face‐to‐face interviews. Patients were asked if they received treatment from any alternative therapist or practitioner in the previous 6 months. Logistic regression was performed to examine associations between demographic and clinical variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 27 publications
1
27
0
5
Order By: Relevance
“…[13] Lastly, from a therapeutic perspective, there are standing concerns of adverse drug reactions (ADRs) between the conventional ARTs and type of CAM used [38,11,44], especially when most studies reported an adjunct use of CAM with ARTs. [31,45] This should also be a concern as the safety and risk factors of possible drug interactions are frequently ignored by PLWHA, as they are much focused on various expected benefits [42] as well as lack of knowledge on safety aspects. [46] Hasan et al in their study among Malaysian PLWHA reported ADRs associated with CAM use, which warranted greater healthcare providers' knowledge regarding the subject.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Lastly, from a therapeutic perspective, there are standing concerns of adverse drug reactions (ADRs) between the conventional ARTs and type of CAM used [38,11,44], especially when most studies reported an adjunct use of CAM with ARTs. [31,45] This should also be a concern as the safety and risk factors of possible drug interactions are frequently ignored by PLWHA, as they are much focused on various expected benefits [42] as well as lack of knowledge on safety aspects. [46] Hasan et al in their study among Malaysian PLWHA reported ADRs associated with CAM use, which warranted greater healthcare providers' knowledge regarding the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews were administered to a convenience sample of 951 adult ( 18 years old) HIV-infected patients who volunteered when asked to participate in an interview, as described previously [22]. The median sample size per site was 59 patients (range 38-172 patients).…”
Section: Subjectsmentioning
confidence: 99%
“…Interviews were conducted with a sample of 951 adult (18 years of age or older) HIV-infected patients who volunteered when asked to participate, as described previously. 22 Initially, a random sample was drawn from deidentified patient lists at each site. Staff at each site determined the sampled patient's name and address, and mailed an invitation to participate.…”
Section: Subject Samplementioning
confidence: 99%